Analisis Kesalahan Partikel Mahasiswa Program Studi Sastra Jepang Universitas Nasional PASIM - Amalia, Aan (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2013)
This research designate about wrong way in used particle (joshi) looked from meaning side,function and how to use in japanesse sentence. In this research data resulted from tes resultand interview for knowing as far as comprehension responden in this thing NationalUniversity of PASIM’s student, about particle (joshi). The result has obtained from thisresearch is the discovery of some wrong way to used the particle and the factors that causethe error, but it was found also an effort to reduce these error. The Mistakes made by therespondents in the use of the particles is due to a lack of understanding of the respondent tothe meaning, function and how to use it, such as the use of particles “de” acknowledgereason, but some of respondents answered incorrectly because they don’t know the meaningand function of that particle, or in using particle ‘ni’ that using in causative (shieki) sentences,in this question majority respondents choose ‘o’ as answers because look at the verb thatusing in the sentence is transitive verb ‘yaru’. The respondents not understand that incausative (shieki) sentence the exact particle for that sentence is ‘ni’